Biomarkers for the early diagnosis of bacterial infection and the surveillance of hepatocellular carcinoma in cirrhosis. (December 2015) - Conti, Fabio; Dall'Agata, Marco; Gramenzi, Annagiulia; Biselli, Maurizio
The early detection of bacterial infections and hepatocellular carcinoma (HCC) could ameliorate the prognosis of cirrhosis. C-reactive protein and procalcitonin are under investigation in the setting of cirrhosis as markers of sepsis. In the attempt to discriminate bacterial infection from systemic inflammation, the role of novel biomarkers such as lypopolysaccharide binding-protein, mid-regional fragment of pro-adrenomedullin and delta neutrophil index are currently in development. Concerning HCC, many studies attempted to evaluate biomarkers in the hope of ameliorating the accuracy of the surveillance based on ultrasound. The use of α-fetoprotein (AFP) has been extensively investigated, as well as other biomarkers expressed in the serum of HCC patients like lens culinaris agglutinin-reactive fraction of AFP, des-γ-carboxy prothrombin, glypican-3, α-l-fucosidase and their combined use.